Empowering Worldwide EFL Learners' Reading Learning Dynamics in the Support of the Jigsaw Technique - Wijaya, Kristian Florensio (Journal of English Language and Pedagogy (JELPA), 2023)
The significant impediments frequently hampering globalized EFL learners from continuing their reading learning enterprises are a higher sense of competitiveness among learning community members, satiation to read plenty of challenging reading texts, and constant perturbing of encountering adverse reading learning situations. These inevitable reading learning obstructions can be better mitigated with the continuous support of the jigsaw technique wherein EFL learners willingly, supportively, and collaboratively address insistent reading learning supports to achieve more gratifying reading learning outcomes as solid teammates. This current small-scale library study is a further attempt by the researcher to exhaustively investigate the influence and crucial role of the jigsaw technique in empowering worldwide EFL reading learning dynamics. To that end, the researchers utilized a thematic analysis approach in reviewing specifically attained research results derived from 20 jigsaw techniques in reading study techniques more trustworthy, robust, and representative findings. The 20 chosen journal articles ranged from 2018 until 2022 to ascertain the validity and reliability of the reviewed research results toward existing EFL reading learning contexts. The thematically categorized research results revealed that the jigsaw technique did not solely make EFL learners more proficient but also avid readers. Therefore, it is vitally essential for worldwide second language educators to commence their daily-based reading learning activities with the endorsement of the jigsaw technique. Keywords: Jigsaw technique; EFL reading; thematic analysis; library study